Human papillomaviruses : IARC Working Group on the Evaluation of Carcinogenic Risk to Humans (World Health Organization, International Agency for Research on Cancer, 2007)
This ninetieth volume of the IARC Monographs on the Evaluation of Carcinogenic Risks to Humans considers human papillomaviruses (HPVs), which were evaluated by a previous Working Group (IARC, 1995). The monograph in the present volume incorporates new data that have become available during the past decade. HPVs represent the most common infectious agents that are transmitted sexually throughout the world; the major risk factors are behaviours associated with sexual activity. Although most infections are asymptomatic and are cleared within a period of 2 years, genital HPV infection can lead to clinical disease, including anogenital warts, cervical neoplasia, cervical cancer and other anogenital cancers. The risk for persistence of infection and progression of the more than 40 genital HPV types to grade 3 cervical intraepithelial neoplasia (CIN3) and cancer differs widely. Persistent infection with carcinogenic HPVs occurs in virtually all cases of cervical cancer.
IARC monographs on the evaluation of carcinogenic risks to humans, ISSN 1017-1606 vol. 90
Keywords: Carcinoma, Papillary; Papillomaviridae; infekce papilomavirem; papilární karcinom; Papillomavirus Infections; gynekologie a porodnictví; karcinogeny; Carcinogens; onkologie